Stable isotope thermometry of the Nanga Parbat-Haramosh Massif and the Kohistan-Ladakh arc, northern Pakistan - Khattak, Muhammad U.K.; Stakes, Debra S.; Shervais, John W.; Arif, Muhammad; Shah, Mohammad Tahir (Journal of Himalayan Earth Sciences, 1995)
The Nanga Parbat-Haramosh Massif in northern Pakistan represents the northernmost exposure of the Indian plate that have been metamorphosed in the Late Tertiary subsequent to the Himalayan collision and over thrusting of the Asian plate onto the Indian plate. The massif a complex mixture of parag- and orthogneisses, of minor metabasics and calc-silicate rocks, and of post-metamorphic pegmatite dikes. The 18O geothermometry results indicate that these gneisses are metamorphosed under peak temperatures of 700+ o C. The 18O isotopic compositions of the rocks and their constituent minerals in the massif and adjacent areas of the Kohistan and Ladakh arc along the Indus and Astore Rivers vary as following: whole rock δ18OSMOW =7-15.3%o; quartz =7.4-16.4%o; feldspar=7-16.1%o; garnet=5.3-13.7%o; biotite=3.9-12.6%o; muscovite=6.7-12.7%o; and hornblende amphibole=4.4-7.2%. The majority of the mineral δ-values follow the “normal” sequence. 18O thermometry results were calculated from 18O fractionations among quartz, garnet, feldspar, biotite, muscovite and amphibole. Fifteen of the sixteen fractionations of Qtz-Gar-pairs (αQG) vary from 2.8%o to 3.8%o giving a range of temperatures from 764oC to 599oC respectively. The 1.0%o variation in fractionation is greater than the expected error and thus indicates a real variation in the temperatures. Among the analyzed minerals, the feldspars, which are isotopically least stable, indicate isotopic resetting during a later event.